Kerokan sebagai Pengobatan Masuk Angin pada Etnis Melayu di Kubu Raya - Saputri, Echa Dwi Retno; Hasanah, Hasanah; Batuallo, Ignasia Debbye (Balale' : Jurnal Antropologi, 2023)
This research is about the traditional kerokan treatment method for ethnic Malays in Kubu Raya Regency. This research aims to find out and analyze people's reasons for choosing the kerokan treatment method nowadays because people still believe in the legacy of their ancestors which has many benefits, looking at the origin of the treatment method focused on the Malay ethnic group, originating from the spread of Javanese ethnicity to Pontianak, knowing the tools and The materials used to carry out the kerokan method for ethnic Malays are very simple, cheap and easy to find, such as using coins, spoons and oil as a lubricant to avoid irritation. The research used a qualitative study which was carried out by asking informants directly and observing them involved. This study uses ethnomedicine as a study paradigm. The results of this research are that traditional medicine, which is still widely used today, has many benefits for the body and tools and materials that are easy to find with just coins and oil so that anyone can use the kerokan treatment method. Catching a cold is understood as a state of illness or an unhealthy body, while kerokan is an attempt to recover.